THE EFFECT OF MURABAHAH AGREEMENT, ENTREPRENEURIAL CHARACTERISTICS, BUSINESS CAPITAL AND MARKETING STRATEGY ON THE DEVELOPMENT OF MSMES IN SIDOARJO REGENCY - Susetyo , Qotrunnada Aisyah Mega; Rahmawati, Imelda Dian (International Journal Multidisciplinary (IJMI), 2025)
Objective: This research aims to analyze the influence of Murabahah contracts, entrepreneurial characteristics, business capital and marketing strategies on the development of MSMEs in Sidoarjo Regency. Method: The sampling technique used in this research was purposive sampling. The sample in this research was 62 food and beverage MSME owners in Sidoarjo district. This research was conducted in Sidoarjo Regency MSMEs. In this study, a 5 point Likert scale was used. This research uses multiple linear regression analysis techniques for hypothesis testing with SPSS version 27 data processing tools. Results: The results of this research indicate that the Murabahah Agreement has an influence on the development of MSMEs. Entrepreneurial Characteristics Influence the Development of MSMEs. Business Capital Influences the Development of MSMEs. Marketing Strategy Influences the Development of MSMEs. Novelty: This research uniquely integrates the analysis of Murabahah contracts, entrepreneurial characteristics, business capital, and marketing strategies simultaneously to examine their influence on the development of food and beverage MSMEs in Sidoarjo Regency, providing a comprehensive perspective that has not been previously addressed in one unified study.